Artificial Intelligence (AI) In Education: Pros and Cons Among Secondary School Teachers in Malang, Indonesia - Rosi, Rois Imron (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3130, 2024)
Artificial Intelligence (AI) became a concern of many scholars including Educators. Some educators believed that AI can be a very sophisticated tool to support teaching and learning processes, but others believed otherwise. Discussion on Implementation of AI in the field of education always stimulates the appearance of pros and cons. This study tries to explore secondary school teacher perspectives on the use of Artificial Intelligence in the field of education. This study explores 15 teachers of secondary school in Malang. In-depth interview was taken to get comprehensive data. The result of this study showed that there are 5 AI tools which became frequently used by teachers, those are: ChatGPT, Grammarly, Canva, Gamma, and Class point. Interestingly, 42% of the informants are using AI for professional purposes like supporting their teaching and learning process. Besides, 33% of the informants are using it for academic purposes like writing the article, news, or other tasks which are able to improve their academic competences. There were also 25% of the informants were used AI for personal purposes which is not correlated to their profession as teachers, like for having fun, trial and error, or out of curiosity. Moreover, the use of Artificial Intelligence in the field of education created two-side of perspectives: pro and con. The pro argued that AI can be fully adapted in secondary school for its numerous benefits for both teacher and student, while the con argued that AI would have many problems if it was implemented.  There are four arguments behind the pros: the use of AI in education proved that teachers are adaptive towards newest technology, it is also able to improve teacher skills and competencies, it also can support teacher’s administrative tasks, and students need to be introduced to the latest technology for their future. On the other side, there are three arguments behind the cons: ethical issues, lack of learning process, and technology dependencies and loss of human interaction.